Chemoenzymatic Synthesis and Function of Chitin Derivatives - Ogata, Makoto (Current Pharmaceutical Design, 2020)
Chitin, abundant biomass found in crab shells and other marine life, has wide applications in the production of food, pharmaceuticals, and cosmetics. Our recent studies have focused on the development of new functional materials by derivatizing chitin oligosaccharides and monosaccharides. For example, we have prepared various derivatives by chemoenzymatic synthesis using N-acetylglucosamine (GlcNAc) or chitin oligosaccharide prepared from chitin as starting materials. First, we have achieved the total synthesis of two secondary metabolites (furanodictine A and B) with neuronal differentiation-inducing activity on PC12 cells by using a simple heatinduced structural transformation of GlcNAc and esterification reaction. Second, we synthesized both a novel inhibitor that has facilitated a re-examination of the reaction mechanism of hen egg-white lysozyme, and a new substrate for assaying lysozyme activity by using chitin oligosaccharides as raw materials. Thus, the development of new materials by simple derivatization of chitin mono- or oligo-saccharides is paving the way for effective use of chitin.
Keywords: chitin derivatives